Synergistic effects of nanoclay and SGF on tribological and dynamic properties of polypropylene composites - Garcia, M. C. R. (2011)
In recent year’s polymer/layered silicate (PLS) nanocomposites have attracted great interest, both in industry and in academia, because they often exhibit remarkable improvement in materials properties when compared with virgin polymer or conventional micro and macrocomposites. These improvements can include high moduli, increased strength and heat resistance, decreased gas permeability and flammability, and increased biodegradability of biodegradable polymers. However these properties are strongly influenced by how the clay is dispersed in the polymer. In this study the synergistic effects in PP+short glass fiber+nanoclay systems in the tribogical and dynamic properties in injection mouldings were analysed. The materials used were a Polypropylene Homopolymer, Nanoclay (montmorillonite layer silicate) for Polyolefin Nanocomposites in percentages of 2%, 6% and 10% and a Polypropylene Homopolymer with content of 10% and 30% of glass fiber reinforced. The various materials systems were characterized in terms of dynamic properties and tribological properties. Several tests were conducted which includes the measurements of coefficient of friction in conditions similar to the ejection phase in injection moulding process. The microstructure of the mouldings was characterized by DSC. Polymer properties are determined by the incorporation of nanoclays, SGF and by processing. Moreover influencing the microstructure of the mouldings and a synergistic effect of the nano and micro reinforcements are also observed.